Violacein from an Antarctic Iodobacter Sp. 7mant and Its Function as Immunomodulator of the Defence Mechanism of Innate Immunity in Fish Cells - Modak-Canobra, B; Valenzuela-Montenegro, B; Blamey-Alegria, J (John Wiley and Sons Inc, 2022)
[No abstract available]